STRATEGI PENGEMBANGAN FASILITAS PARIWISATA BERBASIS KEBERLANJUTAN DI AIR TERJUN JANTUR INAR KABUPATEN KUTAI BARAT - Fadhila, Desi; Isdarmanto; Damiasih (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
Jantur Inar Waterfall is a potential natural tourism destination located in Nyuatan District, West Kutai Regency, East Kalimantan. Despite its strong natural appeal, the area continues to face various challenges in developing adequate and sustainable tourism facilities. This study aims to formulate a sustainability-based tourism facility development strategy that enhances the quality of the destination while preserving the local environment and cultural heritage. A qualitative approach was employed, with data collected through field observations, in-depth interviews with local communities, tourism managers, and regional government representatives. The findings indicate that the development of tourism facilities in Jantur Inar Waterfall must adhere to sustainable tourism principles, including active community participation, the use of environmentally friendly materials, and proper waste management and nature conservation. The proposed strategies include improving basic infrastructure (such as road access and sanitation facilities), constructing culturally rooted supporting facilities, and strengthening community capacity in participatory tourism governance. With an appropriate and sustainable strategy, Jantur Inar Waterfall holds the potential to become a leading natural tourism destination in West Kutai, offering not only economic benefits but also environmental and socio-cultural harmony for the local community.